FAKTOR YANG BERHUBUNGAN TERHADAP CARA MENGATASI MUAL MUNTAH PADA KEHAMILAN TRIMESTER I - Nelfi Sarlis (JOMIS (Journal of Midwifery Science), 2020)
Every pregnant woman in the first trimester experiences nausea and vomiting. This situation is natural and often occurs in pregnancy, especially in the first trimester. Nausea usually occurs in the morning, this case can occur almost 50% of pregnant wowen and many occur at 6-12 weeks. The purpose of this study was to determine the relationship between knowledge and attitudes of pregnant women on how to cope with vomiting nausea in pregnancy trimester 1 in the work area of ​​Payung Sekaki health center in Pekanbaru. This study uses a quantitative method with a cross sectional, so that the number of samples obtained was 71 respondents. Sampling used consecutive sampling technique, nominal and ordinal measuring scales, questionnaire research instruments and univariate and bivariate data collection. Based on the results of the chi square test obtained the knowledge variable is related to how to overcome nausea and vomiting with p = 0.008 where the value of α <0.1 then, Ha accepted means there is a relationship between knowledge and attitudes of pregnant women on how to cope with nausea vomiting while the variable obtained p=0,000 where the value of α<0,1 in the working area of ​​payung sekaki health center in Pekanbaru in 2019. Advised to puskesmas payung sekaki pekanbaru to try to increase public knowledge abaout nausea vomiting in pregnancy and the attitude of pregnant women to overcome nause and vomiting. By providing counseling to pregnant women abaout nausea and vomiting in pregnancy.